Professional issues in speech-language pathology and audiology - Hudson, Melanie W.; DeRuiter, Mark (San Diego, CA : Plural Publishing, Inc., 2021)
The fifth edition of Professional Issues in Speech-Language Pathology and Audiology is a singularly comprehensive resource for students in speech-language pathology and audiology as they prepare for their professional careers. It also serves as a timely source of information for both practitioners and faculty, serving as an updated'state of the professions' desk reference. The book is divided into four major sections: overview of the professions; employment issues; setting-specific issues; and working productively. The information presented in each section provides the reader with a better understanding and a new perspective on how professional issues have been affected by both internal and external influences in recent years including technological advances, demographic shifts, globalization, and economic factors. Chapter authors are recognized subject matter experts, providing a blend of both foundational and cutting-edge information in areas such as evidence-based practice, ethics, finding a job, interprofessional practice, service delivery in healthcare and education, technology, cultural competence, supervision, and leadership. Students reading this book will appreciate how the professions have evolved over time while acquiring a sense of where they are right now as they prepare to enter the professional world. Each of the topics covered in the book will continue to play important roles in the future of audiology and speech-language pathology, providing early career professionals with the requisite knowledge to achieve success in any setting. New to the Fifth Edition New coeditor Mark DeRuiter, PhD, MBA, CCC-A, CCC-SLP 5 new chapters including Professional Accountability (Shelly Chabon and Becky Cornett); Safety in the Workplace (Donna Fisher-Smiley and Cynthia Richburg); Interprofessional Education and Interprofessional Practice (Alex Johnson); Counseling (Michael Flahive); and Advocacy (Tommie Robinson and Janet Deppe) New authors Tricia Ashby, Bob Augustine, Stacy K. Betz, Janet Deppe, Cathy DeRuiter, Mark DeRuiter, Robin Edge, Susan Felsenfeld, Liza Finestack, Michael Flahive, Carolyn Higdon, Kelly M. Holland, Shirley Huang, Susan Ingram, Marie Ireland, Jeffrey Johnson, Pui Fong Kan, Lemmietta McNeilly, Lissa Power deFur, Gail Richard, Steve Ritch, Lisa Scott, and Tina Veale Critical thinking questions at end of each chapter for classroom discussion and examination Updated table of chapter content relevant to the Council for Clinical Certification standards for ASHA Certificate of Clinical Competence Updated acronyms glossary Updated figures and tables Updated and expanded references
Section I. Overview of the Professions. 1. Professions for the Twenty-First Century -- 2. Professional Issues : A View from History -- 3. Establishing Competencies in Professional Education, Certification, and Licensure -- 4. Professional Organizations -- 5. Professional Ethics -- 6. Professional Accountability -- 7. International Alliances -- 8. Applying Evidence to Clinical Practice -- 9. The Future of Science -- Section II. Employment Issues. 10. Workforce Issues -- 11. Finding Employment -- 12. Building Your Career -- 13. Support Personnel in Audiology and Speech-Language Pathology -- Section III. Setting-Specific Issues. 14. Health Care Legislation, Regulation, and Financing -- 15. Service Delivery in Health Care Settings -- 16. Education Policy and Service Delivery -- 17. Service Delivery Issues in Early Intervention -- Service Delivery Issues in Private Practice -- 19. Strategically Promoting Access to Speech-Language Pathology and Audiology Services -- Section IV. Working Productively. 20. Documentation Issues -- 21. Developing Leadership Skills -- 22. Safety in the Workplace -- 23. Overview of Interprofessional Practice and Interprofessional Education -- 24. Child Abuse and Elder Mistreatment -- 25. Working with Culturally and Linguistically Diverse Populations -- 26. Supervision and Mentoring -- 27. Technology for Student Training, Professional Practice, and Service Delivery -- 28. Counseling -- 29. Stress, Conflict, and Coping in the Workplace -- 30. Advocacy.
Includes bibliographical references and index.
Print version record.
WorldCat record variable field(s) change: 650
Keywords: Speech therapy -- Practice; Audiology -- Practice; Speech therapy -- Vocational guidance; Speech therapists -- Professional ethics; Audiology; Speech-Language Pathology; Audiology; Professional Practice; Orthophonie -- Pratique; Audiologie -- Pratique; Orthophonie -- Orientation professionnelle; Orthophonistes -- Déontologie.; Audiologie; Pratique professionnelle; Audiology -- Practice; Speech therapists -- Professional ethics; Speech therapists -- Vocational guidance; Speech therapy -- Practice; Electronic books; Electronic books